Microstructure and mechanical properties of accumulative roll bonded AA6014/AA5754 aluminium laminates - Hausöl, Tina; Höppel, Heinz Werner; Göken, Mathias (Materials Science Forum, 2011)
Among the well-known methods of severe plastic deformation the accumulative roll bonding (ARB) process is most promising for producing ultrafine-grained (UFG) materials with extraordinary mechanical properties at an industrial scale. Besides, it has also been shown that the ARB process can be successfully used to produce multi-component materials with tailored properties by reinforcement or grading, respectively. In this work, laminates with alternating layers of the high strength aluminium alloy AA5754 and the AA6014 alloy, well-known for good formability and high surface quality, were produced by ARB at 230 °C. Microstructural and mechanical investigations were performed after 2, 4 and 6 ARB cycles by means of light and electron microscopy, nanoindentation experiments and tensile testing. After ARB processing an ultrafine-grained microstructure is obtained. The UFG microstructure as well as the local mechanical properties alter with the layer composition. With increasing number of ARB cycles the interfaces between the layers become more and more wavy by shear band formation. Compared to the pure accumulative roll bonded AA6014 the yield and ultimate tensile strength of the multi-component laminates are considerably higher and are only slightly reduced in comparison to the high strength AA5754. In terms of elongation to failure no reduction in ductility is found. The serrated yielding effect, clearly visible in AA5754, is shifted to higher strains or fully disappears, respectively, whereas in AA5754 the magnitude of serrations increases with increasing number of ARB cycles. Combining AA5754 and AA6014 sheets by ARB results in well bonded ultrafine-grained laminates which exhibit a combination of the beneficial properties of the single-component materials: high strength of AA5754 and good surface quality of AA6014.
WW1::889